Quetiapine for the treatment of cocaine use disorder. (1st April 2015) - Tapp, Andre; Wood, Amanda Ernst; Kennedy, Annette; Sylvers, Patrick; Kilzieh, Nael; Saxon, Andrew J.
Highlights: 12-week, double-blind, randomized, placebo-controlled study. Studied efficacy of quetiapine vs. placebo for the treatment of cocaine dependence. Both groups had reductions in self-reported cocaine use and positive urine drug screen results. However, the quetiapine group did not differ significantly from the placebo group. Quetiapine is not supported as an effective treatment for cocaine dependence. Abstract: Background: Cocaine addiction continues to be a significant healthcare issue, yet there are no FDA approved medications for the treatment of cocaine use disorder within the United States. Methods: This 12-week, prospective, double-blind, randomized, placebo-controlled study examined the effectiveness of quetiapine (Seroquel XR™) versus matched placebo for the treatment of DSM-IV cocaine dependence in non-psychotic individuals. Subjects randomized to quetiapine ( N  = 29) were titrated up to a target dose of 400 mg/day of quetiapine, while those in the placebo arm ( N  = 31) were given a matched placebo. All subjects had weekly clinic visits and a cognitive-behavioral therapy group session. Outcome measures included self-report of cocaine use and money spent on cocaine as well as urine drug screens (UDS). Results: The drop-out rate was substantial at 68%. Logistic regression analysis did not find significant differences between groups in predicting end-of trial abstinence, defined as three consecutive weekly negative UDS (13.7% in the quetiapine group versus 12.9% in the placebo group; p  = .92). Based upon a repeated measures analysis of variance, subjects in this study, as a whole, demonstrated reductions in their self-reported use of cocaine, self-reported money spent on cocaine, and number of days per week using cocaine. However, the quetiapine group did not differ significantly from the placebo group. Conclusions: This study did not find group differences between the quetiapine and placebo arms, suggesting that quetiapine is not an efficacious treatment for DSM-IV cocaine dependence.